Who Is an ACE Member? Results From a 2005 ACE Member Survey - Rebecca McGovney-Ingram; Tracy Irani; Ricky Telg (Journal of Applied Communications, 2006)
This study describes the demographics of the population of current, active, U.S.-based agricultural communications practitioner respondents in the Association for Communication Excellence in Agriculture, Natural Resources, and Life and Human Sciences (ACE) in an effort to gain a better understanding of membership demographics. In fall 2004, the researchers mailed questionnaires to 510 ACE members. Returned questionnaires were accepted through January 2005 and processed in the following months. The overall response rate was 35.1% (n = 179). Analysis of demographic results showed that the majority of U.S. respondents were female (58.8%, n = 104) and Caucasian (95%, n = 168). More than 80% of the respondents worked for an agricultural institution of higher education. When asked to select the ACE special interest group (SIG) to which their job function was most closely related, most respondents selected the writing / media relations /marketing and publishing/graphic design/photography SIGs. When compared with data from other communications studies, the demographic profile of ACE members demonstrated by these survey results suggests that employment trends within ACE are similar to those seen in other communications fields in the United States. Understanding the demographics of a professional association like ACE might make it easier for members to participate in and help lead the organization.